Fundamentals of chemistry - Redmore, Fred H. (Englewood Cliffs, New Jersey : Prentice-Hall, 1979)
The emphasis is on the fundamental principles of chemistry. Once the student has mastered these fundamentals, additional topics can be introduced by the instructor as time and ability of students allows.
Includes index.
Keywords: CHEMISTRY